2007
DOI: 10.1111/j.1742-4658.2007.05836.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of nuclear DNA by DNase II‐like acid DNase in cortical fiber cells of mouse eye lens

Abstract: The eye lens is composed of fiber cells that differentiate from epithelial cells on its anterior surface. In concert with this differentiation, a set of proteins essential for lens function is synthesized, and the cellular organelles are degraded. DNase II‐like acid DNase, also called DNase IIβ, is specifically expressed in the lens, and degrades the DNA in the lens fiber cells. Here we report that DNase II‐like acid DNase is synthesized as a precursor with a signal sequence, and is localized to lysosomes. DNa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 37 publications
5
63
0
Order By: Relevance
“…Several potential mechanisms have been reported, which include the ubiquitin-proteasome system (28,41,42), 15-lipoxygenase (43), and DNase II-like acid DNase (DLAD) (44). Among them, DLAD, a lysosomal DNase (45,46), is required for degradation of nuclear DNA in the lens (44). Thus, it is likely that the lysosome is involved in degradation of nuclear DNA in a manner different from any known types of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential mechanisms have been reported, which include the ubiquitin-proteasome system (28,41,42), 15-lipoxygenase (43), and DNase II-like acid DNase (DLAD) (44). Among them, DLAD, a lysosomal DNase (45,46), is required for degradation of nuclear DNA in the lens (44). Thus, it is likely that the lysosome is involved in degradation of nuclear DNA in a manner different from any known types of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…They are active and present in lysosome (but found in other organelles) and believed to act as a barrier to transfection for DNA or vectors entering the cell by endocytosis [8] and may degrade foreign DNAs and play a role in the replication of DNA [9]. Recent studies have identified many DNases that are active at neutral pH such as caspase-activated DNase (CAD) [10], and endonuclease G [11] that are found in mammals, though a few researchers have concentrated on insect acid [12]. The function of DNases within the small intestine is debated and very few researchers purified DNases from small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…DLAD (DNase II-like acid DNase, also called DNase IIb) has a 38% amino acid sequence identity with DNase II (Shiokawa and Tanuma 1999) and is also localized to the lysosomes (Nakahara et al 2007). Unlike DNase II, which is ubiquitously expressed in various tissues and cells, DLAD is specifically expressed in fiber cells of the optic lens (Fig.…”
Section: Dlad a Dnase In Lens Fiber Cellsmentioning
confidence: 99%
“…As the epithelial cells differentiate into fiber cells, they synthesize lens-fiber-specific proteins such as crystallins. The DLAD gene is also activated during this differentiation process (Nakahara et al 2007). …”
Section: Dlad a Dnase In Lens Fiber Cellsmentioning
confidence: 99%
See 1 more Smart Citation